Slope Stability Analysis of the Mahakam Monthly Pit Highwall Design at PT Arta Bumi Sakti Insani BaraPerkasa Site East Kalimantan - Muhammad Faisal Siddiq; Yossa Yonathan Hutajulu; Ferdinandus Ferdinandus; Nuansa Mare Apui Ganang; Yusias Andri (G-Tech: Jurnal Teknologi Terapan, 2025)
PT Arta Bumi Sakti operates within the mining sector, focusing on the Insani Baraperkasa. A major challenge in open-pit mining in this area is maintaining the stability of highwall slopes, particularly in the 2025 Mahakam monthly pit design. This study aims to evaluate slope stability in the highwall region using the Limit Equilibrium Method through the Bishop Simplified, Janbu Simplified, Morgenstern Price, and Spencer. Geotechnical parameters were obtained from laboratory tests and interpretations of geotechnical drilling data, including unit weight, cohesion, internal friction angle, UCS, and GSI. Software was used to analyze the slope and calculate safety factors while considering groundwater levels, earthquake loads, and ground pressure across two representative cross-sections. The results show that both cross-sections have safety factor values exceeding the minimum threshold established by the Ministry of Energy and Mineral Resources Regulation No. 1827 K/30/MEM/2018, namely, FS > 1.1 and PoF < 20%. Thus, mining activities in this period can be conducted safely. In addition, the Spencer Method, which simultaneously satisfies stability in terms of force and momentum, provides stable results, this can be used as the basis that the Spencer can be used as the main method in the analysis of slope stability in the location.